ARTIFICIAL INTELLIGENCE AND LABOR MARKET DISRUPTION: ECONOMIC PERSPECTIVES - Asrayev , Shavkat (Effective scientific journals, 2025)
Artificial intelligence (AI) is reshaping global labor markets by transforming employment structures, productivity, and income distribution. As automation advances, routine tasks decline while demand for high-skill, technology-driven roles increases. This study analyzes the economic implications of AI adoption, focusing on productivity, wage polarization, and employment shifts across industrial and emerging economies. Using mixed methods and global labor data, the findings reveal that although AI enhances productivity, it amplifies inequality in the absence of adaptive labor and education policies. The research concludes that sustainable integration of AI depends on human capital investment, lifelong learning, and inclusive policy frameworks that harness AI’s potential as a driver of equitable economic growth.